Class I Preparation: Instructional Video - Shalizeh Azizi Patel; Ryan L. Quock; Juliana A. Barros; Darrel Gonzales; Timothy C. Woernley; Martha G. Orozco; Gary N. Frey (Association of American Medical Colleges, 2013)
Abstract Introduction This resource is intended to serve as an adjunctive tool for teaching operative dentistry. The centerpiece of the resource is a 4-minute instructional video, which presents basic technique for a Class I preparation. The general target audience is dental students, and the video should be presented in the context of a comprehensive operative dentistry curriculum. Methods The video conveys operative concepts via a variety of formats: text, photos, and live video, all with audio narration. Students can watch the video on their personal computer/media device as a form of self-study or review. The video can also be projected as a stand-alone presentation before a group of viewers in teaching and/or calibration scenarios. It can be easily paused during presentation to engage in reflection on and discussion of previously presented information. In addition to the video, a multiple-choice quiz is provided to allow the audience to self-assess. Results This video has become a powerful medium for effectively illustrating operative procedures at our institution. By viewing the video in advance, students are more attentive during lectures and seem to ask better questions. They have also become more efficient during laboratory sessions and are able to better self-assess. Discussion This resource was developed specifically in response to consistent student requests for video demonstration of the procedures covered in operative dentistry courses. Students seemed to be especially interested in the ability to review theory and techniques as many times as necessary before actual live patient encounters. With this in mind, the goal was to create a self-contained resource that could be easily accessible for its audience. The self-contained nature of the video makes it easily adaptable to a number of learning scenarios. In addition, the video can be used as a review in preparing for regional board exams.